B2B commitment building in emerging markets: the case of Brazil. Issue 2 (2nd April 2016) - Graça, Sandra S.; Barry, James M.; Doney, Patricia M.
Abstract : The research examines the suitability of relationship marketing paradigms to emerging markets (EMs) through the lens of communication, relationship benefits and commitment. Using the U.S. as a developed nation sample and Brazil as a proxy for EM countries like the BRIC nations, a B2B buyer–supplier commitment-building model is conceptualized and tested for context-specific boundaries. The study compares communication behaviors and relationship benefits along functional, psychological and social dimensions to discern the evaluation process and governance mechanisms influenced by an EM buyer's institutional environment. Results showed that buyers from relation-based EMs like Brazil base their relationship commitment more on the psychological attributes of the partnership, while a buyer's commitment-building process in rule-based, developed nations like the US is largely influenced by functional attributes.